CCL24 and Fibrosis: A Narrative Review of Existing Evidence and Mechanisms - Raanan Greenman; Chris J. Weston (Cells)
Tissue fibrosis results from a dysregulated and chronic wound healing response accompanied by chronic inflammation and angiogenesis. Regardless of the affected organ, fibrosis shares the following common hallmarks: the recruitment of immune cells, fibroblast activation/proliferation, and excessive extracellular matrix deposition. Chemokines play a pivotal role in initiating and advancing these fibrotic processes. CCL24 (eotaxin-2) is a chemokine secreted by immune cells and epithelial cells, which promotes the trafficking of immune cells and the activation of profibrotic cells through CCR3 receptor binding. Higher levels of CCL24 and CCR3 were found in the tissue and sera of patients with fibro-inflammatory diseases, including primary sclerosing cholangitis (PSC), systemic sclerosis (SSc), and metabolic dysfunction-associated steatohepatitis (MASH). This review delves into the intricate role of CCL24 in fibrotic diseases, highlighting its impact on fibrotic, immune, and vascular pathways. We focus on the preclinical and clinical evidence supporting the therapeutic potential of blocking CCL24 in diseases that involve excessive inflammation and fibrosis.